The Response of the Root Apex in Plant Adaptation to Iron Heterogeneity in Soil - Li, Guangjie; Kronzucker, Herbert J.; Shi, Weiming (Frontiers in Plant Science, 2016)
Iron (Fe) is an essential micronutrient for plant growth and development, and is frequently limiting. By contrast, over-accumulation of iron in plant tissues leads to toxicity. In soils, the distribution of Fe is highly heterogeneous. To cope with this heterogeneity, plant roots engage an array of adaptive responses to adjust their morphology and physiology. In this article, we review root morphological and physiological changes in response to low- and high-Fe conditions and highlight differences between these responses. We especially focus on the role of the root apex in dealing with the stresses resulting from Fe shortage and excess.